Physical development and sociocultural context influences on children’s physical activity - Alessandro Hervaldo Nicolai Ré; Maria Teresa Cattuzzo; David Stodden; Guilherme dos Santos; Albert Lucas Olinto Tertuliano; Carlos Bandeira de Mello Monteiro; Diogo Henrique Constantino Coledam; Anthony David Okely (Revista Paulista de Pediatria)
Abstract Objective: To examine the predictive strength of cardiorespiratory fitness (CRF), motor competence (MC), maternal educational status, and parental perception of their children’s favorite leisure activities for meeting physical activity (PA) guidelines of each gender among children aged 3–6 years. Methods: This is a cross-sectional study with 367 preschoolers (53% girls), assessing CRF (PREFIT 20m shuttle run), MC (battery of motor skills), PA (accelerometry), maternal education and parental perception of children’s preferred leisure (questionnaires). Factorial analysis of covariance, multiple logistic regression, and chi-square tests were conducted. Results: In both genders, CRF was associated with meeting PA guidelines (girls: odds ratio [OR] 1.10; 95% confidence interval [CI] 1.03–1.18; boys: OR 1.12; 95%CI 1.05–1.19), independently of maternal education or parental perception of children’s leisure activities. For girls, active leisure with balls (OR 28.91; 95%CI 6.88–121.50) and without balls (OR 4.32; 95%CI 1.95–9.57) enhanced the odds of compliance with PA guidelines, without effect of maternal education. For boys, maternal education was inversely associated with meeting the PA guidelines. Boys of lower-educated mothers were more likely to have activities with balls as favorite leisure, which was a stronger predictor and enhanced the odds of meeting the guidelines (OR 4.09; 95%CI 1.71–9.79) regardless of maternal education. Boys had a higher prevalence of active leisure with balls than girls (42.8 vs. 7.7%). Conclusions: Regardless of CRF or MC, family and sociocultural circumstances influenced PA according to gender. Health policies should encourage equal gender participation in culturally significant sports or activities of a particular region/country, specifically within the family context.